Compensation of unbalanced low-voltage grids using a photovoltaic generation system with a dual four-leg, two-level inverter - Fernao Pires, Vitor (2022)
In this paper, a grid-connected photovoltaic (PV) generation system is proposed with the purpose of providing support to low-voltage grids, namely through the elimination or attenuation of the grid imbalances. This compensation must consider the load types, which can be either linear or non-linear, and whether the reactive power and current harmonics generated by the non-linear loads need to be compensated in addition to the unbalanced active power. This must be well considered, since the compensation of all aspects requires oversized PV inverters. Thus, the different unbalanced compensation schemes are addressed. Several schemes for the generation of the inverter current references taking into consideration the compensation and load type are presented. For this PV generation system, a dual four-leg, two-level inverter is proposed. It provides full unbalanced compensation owing to the fourth leg of the inverter and also extends the AC voltage, which is important when this compensation is required. To control this inverter, a control scheme for the inverter that considers several compensation factors is proposed. A vector voltage modulator associated with the controller is another aspect that is addressed in the paper. This modulator considers the balance between the DC voltages of the inverters. Several compensation schemes are verified through computational tests. The results validate the effectiveness of the proposed PV generation system.